DEVELOPMENT IN PUNISHMENT FOR HARMLESS MURDER CALLED RAPE: A STUDY - khandare, Jayashree; Sinha, Shivangi (International Journal of Psychosocial Rehabilitation, 2020)
Rape in simple terminology is an act which is done without a person‟s concerned, and is completely against the society. It is a sexual assault which is been conducted by people or with the group of people‟s using physical force or manipulation, with or without the person‟s consent. “Rape”, was a term which was first introduced in India in the “Indian Penal Code” in 1860 by Lord Macaulay which got it genesis from the 1st Law Commission Report under his chairmanship. This is one such offence which keeps on changing its shape in the statute and legislation according to the environment and as the society develops. People change their perspective, and so the law needs to be evolved accordingly. Dating back the history we had incidents such as Mathura custodial rape case, which eventually brought the Criminal Law (Second Amendment) Act of 1983. Furthermore, we had PIL‟s filed by the NGO‟s to widened the scope of the term „sexual intercourse‟ as mentioned under the section 375 of IPC. Now after the 2013 amendment in the criminal law, the rape laws have tried to take a more austere step.In this paper, we will be dealing with all these aspects in details, by using certain ratios of the cases decided. We can see that how the evolution of the law took place with the passage of time, and the amendments took place according to the societal perspectives.